Structure and spatial pattern of land uses patches in the Zagros Mountains region in the west of Iran - ARASH KARAMI; KIOMARS SEFIDI; JAHANGIR FEGHHI (Biodiversitas Journal of Biological Diversity, 2014)
Karami A, Sefidi K, Feghhi J. 2014. Structure and spatial pattern of land uses patches in the Zagros Mountains region in the west of Iran. Biodiversitas 15: 53-59. Landscape ecology as a new interdisciplinary science, concepts, theories and methods provides for evaluation and management of land. Quantification of landscape patterns has key role in the interpretation and modeling of spatial and chronically variation of land uses. This study carried out in the Zagros vegetative region in the west of Iran to quantify structure and spatial pattern of land uses and forest fragmentation in the Zagros Mountains region. The mosaic analysis method was used for quantifying landscape metrics. Totally 2783 land use patches were recorded in the study area. The most of the patches were agricultural area and the lowest number of patches recorded for rivers. Diversity indices analysis showed agricultural land use has highest diversity in comparing with other land uses. Rangeland use has distributed in the central region of the study area. Despite the high density agriculture and rangeland a lot of potentials there are two conversions this land as a sustainable ecosystem (forests, agriculture integrated, and rangelands), that can be by applying as an appropriate method in management and control policies and converting artificial land uses to the natural or semi natural land uses according to the advantages of such land uses in view of sustainability. We conclude that fragmentation of natural land uses such forest and rangelands should be reducing and maintain large patches of natural vegetation to sustainable land management in this region.